The effect of dietary supplementation of Lycium barbarum leaves on the growth performance, organ indexes and intestinal microflora of rats - Guo, Yindi; Liu, Jie; Tuo, Qiang; Zhang, Dongtao; Wanapat, Metha; Xin, Guosheng (Frontiers in Veterinary Science, 2024)
This study was conducted to investigate both fruit and different levels of leaf supplementation on the growth performance, organ indices and intestinal microflora of rats. Twenty-five healthy male Sprague–Dawley rats were randomly divided into five groups. The rats in the control (NC) and positive control (PC) groups were fed by gavage a basal diet and a basal diet with 4 g/kg of L. barbarum fruit homogenate, respectively. The test (LD, MD, and HD) groups were fed basal diets with additional 2, 4, and 8 g/kg of L. barbarum leaf homogenate, respectively. The feeding period was 35 d. The result revealed that the rats in the LD group had the highest average weight gain (p < 0.05). The cardiac and renal indexes in the LD and MD groups were significantly higher than in NC group, respectively (p < 0.05). Diversity analysis revealed that adding low concentrations of L. barbarum leaf homogenates markedly reduced the Shannon index of the rats cecum (p < 0.05). The relative abundance of Verrucomicrobiota was higher in the LD group than those in other groups (p < 0.05). The relative abundance of Actinobacteriota was found significantly higher in PC group than others (p < 0.05). The relative abundance of Akkermansia in LD group was the highest (p < 0.05). The relative abundance of Romboutsia in the PC group was considerably higher than that in other groups. The relative abundance of Candidatus_Saccharimonas in the supplementation groups was appreciably lower than those found in other groups. The relative abundance of Alloprevotella was significantly lower in PC, LD, and MD groups than in NC and HD groups (p < 0.05). The relative abundance of Oscillibacter was significantly higher in HD group than in other groups (p < 0.05). Thus, L. barbarum leaf homogenate fed to rats could increase their growth performance, internal organ weights and additionally enhance the relative abundance of beneficial bacteria. Therefore, based on the obtained data in the current study, a dose of L. barbarum leaf homogenate supplemented with 2 g/kg in diet is recommended, however, further studies are required to confirm, especially in animals.